Human apolipoprotein A-I natural variants: molecular mechanisms underlying amyloidogenic propensity - Ramella, Nahuel (2012)
Human apolipoprotein A-I (apoA-I)-derived amyloidosis can present with either wild-type (Wt) protein deposits in atherosclerotic plaques or as a hereditary form in which apoA-I variants deposit causing multiple organ failure. More than 15 single amino acid replacement amyloidogenic apoA-I variants have been described, but the molecular mechanisms involved in amyloid-associated pathology remain largely unknown. Here, we have investigated by fluorescence and biochemical approaches the stabilities and propensities to aggregate of two disease-associated apoA-I variants, apoA-IGly26Arg, associated with polyneuropathy and kidney dysfunction, and apoA-ILys107-0, implicated in amyloidosis in severe atherosclerosis. Results showed that both variants share common structural properties including decreased stability compared to Wt apoA-I and a more flexible structure that gives rise to formation of partially folded states. Interestingly, however, distinct features appear to determine their pathogenic mechanisms. ApoA-ILys107-0 has an increased propensity to aggregate at physiological pH and in a pro-inflammatory microenvironment than Wt apoA-I, whereas apoA-IGly26Arg elicited macrophage activation, thus stimulating local chronic inflammation. Our results strongly suggest that some natural mutations in apoA-I variants elicit protein tendency to aggregate, but in addition the specific interaction of different variants with macrophages may contribute to cellular stress and toxicity in hereditary amyloidosis.